Lamb feeding experiments, Studies carried on by the Department of Animal Husbandry and the Garden City Branch Experiment Station - Menzies, C.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2011)
October 27, lambs were weighed, lotted, and started on test. Lambs were faced and tagged. Seventy-five lambs were shorn and all lambs, except those in lot 9, were drenched with 6 cc. of Trivermol drench. Half the lambs in each lot were implanted with 3 mgs. stilbestrol at the start of the test. Final weights were taken February 12 after 108 days of feeding. Lambs not shorn in October were shorn February 13. Standard feedlot ration consisted of whole grain sorghum, sorghum silage, alfalfa hay, and cottonseed meal. Lot 7 served as the feedlot control. Lot 9 was not drenched and was fed 30 rngs. hygromycin per lamb per day. Lot 10 was given 2.5 mgs. Tran-Q tranquilizer per lamb per day and lot 2 was drenched twice. December 30, 30 lambs in the "jackpot" lot were started on un exploratory cobalt study. Two hundred lambs were grazed on volunteer wheat pasture for the entire test. Fifty of these, lot 8, were fed Tran-Q tranquilizer in salt. Seventy-five of the remaining lambs were shorn at the start of the test. Twenty-five of the shorn lambs and 25 unshorn lambs were reimplanted with 3 mgs. stilbestrol 61 days after the start of the test. Lambs in lot 3 were grazed on irrigated wheat pasture.
Keywords: Sheep; Feedlot; Implant; Wheat pasture